Mineral composition of Carica papaya Linn extracts - Nafiu, Bidemi Abdulrazaq; Abd. Malik, Izzati; Rahman, Mohammad Tariqur (2010)
Investigation was carried out on the nutritionally essential mineral elements contents of seed (CPS), endocarp (CPF) and epicarp (CPP) of papaya extracts. Both aqueous (h2o) and PBS extracts were analyzed to determine the contents of 8 minerals namely Ca, Mg, Na, Fe, Mn, Zn, Ag and Se using atomic absorption spectrophotometry (AAS) following microwave-assisted digestion based on the mixture of nitric acid-hydrogen peroxide procedure. The result showed that Ca was the most abundant in papaya fruit as a whole with larger amount found in the aqueous extract of papaya epicarp (CPP h2o) although CPS PBS extract contains more Fe as compared to other extracts analysed. The higher concentrations of Na, Mn, Mg, Se and Zn were found in CPF PBS, CPS h2o, CPF PBS and CPF h2o respectively. Ag was determined for the first time though it was not detected. some of these essential elements contained in papaya at higher level might play vital role in biochemical/enzymatic processes and are likely to be responsible for its reported medicinal properties such as wound healing.